NGHIÊN CỨU TÁC DỤNG GIẢM LIPID MÁU CỦA TỎI ĐEN HLG TRÊN LÂM SÀNG - Hoàng, Đức Hậu; Dương, Đức Nghĩa (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
REDUCTION OF BLOOD LIPID PARAMETERS BY SUPPLEMENTATION OF BLACK GARLICThe study was carried out in 30 patients with mild hypercholesterolemic. The results showed that total cholesterol decreased from 6,27 ± 1,01 mmol/l to 5,75 ± 0,81 mmol/l (p < 0.05) after using black garlic during 4 weeks with 6 grams per day. In addition, after 4 weeks consumption black garlic, the triglycerides level significantly went down from 23 ± 0,74 mmol/l to 2,09 ± 0,58 mmol/l (p < 0.05) and low-density lipoprotein cholesterol level was also reduced from 3,38 ± 0,44 mmol/l to 3,11 ± 0,55 mmol/l (p < 0.05). The data demonstrated the effectiveness of black garlic in supporting the treatment for patients with mild hypercholesterolemic.